Modeling and simulation of coffee bean heating during roasting: effect of heat generation - Bustos-Vanegas, Jaime Daniel; Martins, Márcio Arêdes; Corrêa, Paulo Cesar; Baptestini, Fernanda Machado; de Oliveira, Gabriel Henrique Horta (Frontiers in Food Science and Technology, 2025)
The temperature of the coffee bean during roasting determines the sensory and nutritional quality of the beverage. Thus, evaluation of the effect of heat generated by evaporation and oxidation reactions during roasting is mandatory to elucidate this process. This work aimed to model and simulate heating. It was considered a lumped analysis on developing a physical model for estimating the temperature of the coffee bean. The model was fitted to experimental data. When evaporation is negligible, the model overestimates the temperature during the exothermic reaction period, beginning at 150°C, and up to the consumption stage of the reagents. By contrast, when exothermic reactions are ignored, the model underestimates the temperature of the bean due to cooling caused by evaporation. The temperatures estimated by the model showed R2 values between 0.973 and 0.994 at different roasting temperatures. The model can be used as an optimization and controlling tool in the roasting process.